2018
DOI: 10.1007/s13765-018-0394-0
|View full text |Cite
|
Sign up to set email alerts
|

I-motif-coated exosomes as a pH-sensitive carrier for anticancer drugs

Abstract: Nature-derived exosomes have been noted as emerging carriers for anticancer drugs. In this study, as a proof-of-concept, the anticancer drug doxorubicin (Dox) was loaded onto i-motif-modified exosomes (Exo-i-motif) to deliver Dox to cancer cells efficiently. The doublestranded biotin-i-motif/flare (ds-i-motif-bio)s efficiently released Dox in an acidic pH-responsive manner within 1 h. Based on gel electrophoresis, it was clearly confirmed that ds-i-motif-bio successfully interacts with biotin-conjugated exosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Application of cytosine-rich telomeric fragments of DNA as components of drugs carriers has been described in several studies [16][17][18][19][20][21][22]. This is because such oligonucleotides reveal interesting properties of reversible folding/unfolding in response to pH change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of cytosine-rich telomeric fragments of DNA as components of drugs carriers has been described in several studies [16][17][18][19][20][21][22]. This is because such oligonucleotides reveal interesting properties of reversible folding/unfolding in response to pH change.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Kim et.al. [20] utilized iM modified exosomes as platforms for doxorubicin (DOX) storage and release with iM folding/unfolding property as a key factor for controlled release of DOX. Intercalation of DOX within dsDNA fragments attached to gold nanoparticles was studied in the work by Park et.al.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using the pH-responsive drug release ability of i-motif system have been reported [6,7,8,9]. An i-motif and G-quadruplex-modified gold nanoparticle (AuNP) was developed for anti-tumor therapy via chemotherapy by DOX, photothermal therapy (PTT) by AuNP, and photodynamic therapy (PDT) by photosensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…In another case, i-motif was grafted on exosome using biotin-streptavidin interaction to deliver DOX by intercalation in their double-stranded structure. In acidic condition, DOX release from exosome was triggered by the formation of i-motif, disintegrating double-stranded DNA structure [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biologically derived vesicles, e.g., cell-derived vesicles and microvesicles, have been intensively investigated as one of the alternatives for synthetic particulate systems. In particular, exosomes (EXOs) have been considered promising drug carriers because of their aqueous stability, homogeneous diameter, and biocompatibility [11][12][13]. In a previous study, serum derived EXOs had a narrow size distribution of approximately 50 nm as well as high production yield [14].…”
Section: Introductionmentioning
confidence: 99%